Hiro - Robin Davies; W.Awdry (London, Egmont, 2010)
This is a story about an old engine called Hiro, who was lost for many years. Thomas and Percy wanted to help Hiro get back on the rails again. But would the be able to save him from being sent for scrap?
Keywords: Storybook